Pengaruh Model Creative Problem Solving (CPS) Terhadap Kemampuan Berpikir Kritis Matematis Pada Materi Relasi dan Fungsi - Maria, Sonta (Unika Santo Thomas Medan, 2018)
The purpose of this study was to determine the effect of the Creative Problem Solving (CPS) learning model on students' critical thinking skills in the material relations and functions and student responses to the CPS learning model. This research is a quasi-experiment. The results of the study obtained a regression equation Y = 62.1621 + 15.7094X with a coefficient of determination of 23% which indicates that there is a positive influence. The average value of mathematical critical thinking abilities of students who take part in the learning with the CPS model is 77.87, while expository learning is 62.16. Analysis of student responses to the CPS learning model was obtained: (1) 97.3% expressed interest in the CPS learning model and 2.7% expressed no interest; (2) A total of 98.2% stated that there were benefits obtained by students using the CPS learning model and 1.8% stated that there were no benefits obtained; (3) A total of 90.74% stated that there were no obstacles experienced during the learning process using the CPS learning model and 9.26% stated that they experienced problems; (4) 96.22% expect that the CPS learning model is used in the learning process and 3.78% do not expect to be used. So, it was concluded that the student response was very positive towards the CPS learning model because the percentage that stated the agreement was 95.62% greater than the one who expressed disagreement namely 4.38%.